267 When investigating stroke is a waste of time. Issue 6 (27th May 2022) - Cook, Sarah; Warner, Graham
Abstract : Young stroke should alert clinicians to investigate for unusual causes. A previously well 43-year-old Caucasian female presented with 2 days of punctuated left sided weakness and sensory inattention. MRI demonstrated multiple territory infarcts, predominantly on the right side. With no vascular risk factors, high dose steroids were commenced assuming primary angiitis of the CNS (PACNS). Blood tests including ESR, HIV, an autoimmune and thrombotic screen and blood cultures were negative. A 24-hour ECG and TOE failed to identify an embolic source, though interval MRIs plus CT angi- ography revealed evolving cerebral and splenic infarcts. A DOAC was added. Retinal angiography did not support PACNS, nor did PET-CT though it did show an avid uptake large pelvic mass. Tumour markers CA 125 and CA 19–9 were markedly raised. Urgent gynaecological review was sought but the patient developed florid aortic regurgitation and further cerebral infarcts despite heparinisation. Repeat echocar- diography this time showed a dysplastic aortic valve. Pelvic mass excision confirmed adenocarcinoma. Non-bacterial thrombotic (marantic) endocarditis (NBTE) is a rare cause of embolic stroke. Systemic wasting from associated malignancy is hinted at in the etymology (Greek. marantikos = to waste away). Our patient remained 'well' and only the valve wasted away. Friable valve lesions in NBTE are prone to embolization and removal of the pro-coagulant tumour is the most effective treatment. sarah.cook18@nhs.net